A caracterização do Vínculo Empregatício na Justiça do Trabalho da Região de Passo Fundo : aspectos jurídicos e históricos no período de 1998 a 2008 - Marangon, Elizete Gonçalves (2009)
This study addresses the defining elements of the employment bond. The issue is about verifying, through the inductive method, whether the sentences in the 1998 2008 period in the Labor Justice of Passo Fundo recognizes or not the employment bond, based on the specific principles of the Labor Law and on the human dignity, assured in the Federal Constitution, and which constitutes the theoretical point of investigation. The perception of the social rights is contextualized, among them the work rights created during the Vargas Era, from the integration between History and Law, demonstrating the need and utility of the multidisciplinary connection for a critical analysis of the contrast in making use of the work force dissociated of the work rights